Salmonella enterica subsp. enterica serovar Enteritidis harbours ColE1, ColE2, and rolling-circle-like replicating plasmids - Gregorova, Daniela; Matiasovicova, Jitka; Sebkova, Alena; Faldynova, Marcela; Rychlik, Ivan (Canadian journal of microbiology, 2004)
Using DNA hybridization, at least three distinct groups of low molecular mass plasmids were identified in Salmonella enterica subsp. enterica serovar Enteritidis. After sequencing representative plasmids from each group, we concluded that they belonged to ColE1, ColE2, and rolling-circle-like replicating plasmids. Plasmid pK (4245 bp) is a representative of widely distributed ColE1 plasmids. Plasmid pP (4301 bp) is homologous to ColE2 plasmids and was present predominantly in single-stranded DNA form. The smallest plasmids pJ (2096 bp) and pB (1983 bp) were classified as rolling-circle-like replicating plasmids. Both encoded only a single protein essential for their own replication, and they must have existed in an unusual molecular structure, as (i) they were capable of hybridization without denaturation, (ii) their DNA could be linearized with S1 nuclease, and (iii) even after such treatment, the ability to hybridize without denaturation did not disappear.
Keywords: denaturace nukleových kyselin; DNA bakterií; Salmonella enteritidis; Sequence Analysis, DNA; endonukleasy specifické pro jednořetězcové nukleové kyseliny; DNA, Single-Stranded; plazmidy; Single-Strand Specific DNA and RNA Endonucleases; jednovláknová DNA; Bacteriocin Plasmids; sekvenční analýza DNA; DNA Replication; DNA, Bacterial; bakteriocinové plazmidy; replikace DNA; Nucleic Acid Denaturation; extrachromozomální dědičnost; Nucleic Acid Hybridization; hybridizace nukleových kyselin; Plasmids; Extrachromosomal Inheritance